Analysis of Delays in the Handover of Infrastructure, Facilities, and Utilities by Housing Developers in the City of Semarang - Aurellia Sabryna Imanda (Faculty of Law, Universitas Negeri Semarang, 2025)
The handover of infrastructure, facilities, and utilities (PSU) by housing developers must be carried out on time in accordance with Law Number 1 of 2011. In the City of Semarang, the PSU handover is specifically regulated under Law Number 7 of 2021. In practice, however, the handover of PSU is often delayed by housing developers. This delay causes confusion for the government when attempting to manage PSU within a housing complex, as full control remains with the developer. This study analyzes the factors behind the delays in PSU handovers by housing developers in the City of Semarang, as well as the resulting impacts on developers, residential environments, and homeowners. The findings indicate that the causes of delays can be categorized into internal factors—such as the developer’s ongoing interests in a housing area—and external factors—such as the unavailability of regional budget (APBD) funds from the government to manage the PSU